Online tutoring in pandemic: An investigation on students’ mathematics anxiety and learning motivation - Syafika Ulfah; Khoirunnisa Khoirunnisa; Collins Bekoe (Department of Mathematics Education, Faculty of Mathematics and Natural Sciences, UNY, 2021)
Learning activities should be shifted from offline to online mode as a consequence of the COVID-19 pandemic. Several previous studies have stated that this situation affects the psychology of students. This study aimed to examine mathematics anxiety and learning motivation of junior high school students based on the availability of online tutoring support during the COVID-19 pandemic. We employed a survey method by distributing a Google Form link containing a questionnaire to a public junior high school in East Jakarta, Indonesia. The questionnaire consisted of 22 items of mathematics anxiety and 23 items of learning motivation with a 5-point Likert scale. A total of 365 eighth-grade students were involved in this study. Data analysis used descriptive analysis, Mann-Whitney test, and correlation analysis. Our study revealed a significant difference between students who took and did not take online tutoring. Furthermore, the study also found a negative relationship between mathematics anxiety and learning motivation. The students who took online tutoring had a low level of mathematics anxiety and a very high level of learning motivation.